Asuhan Keperawatan Jiwa Pada Tn. F Dengan Masalah Utama Gangguan Sensori Persepsi: Halusinasi Pendengaran Akibat Skizofrenia Tak Terinci Diruang Gatot Kaca RSJD dr. Amino Gondohutomo Provinsi Jawa Tengah - Umu Aiman; Slamet Wijaya (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Background: Schizophrenia is a psychiatric disorder characterized by positive psychotic symptoms (such as hallucinations) and negative symptoms accompanied by cognitive decline. Auditory hallucinations represent the most common positive symptom, occurring in more than 75% of patients with schizophrenia. Objective: This study aimed to describe the comprehensive nursing care for Mr. F with a primary problem of perceptual sensory disorder: auditory hallucinations due to undifferentiated schizophrenia at Gatot Kaca Ward, RSJD dr. Amino Gondohutomo, Central Java Province. Method: This study used a descriptive method with a nursing process approach, including assessment, nursing diagnosis, intervention planning, implementation, and evaluation. Data collection was carried out through interview, observation, and literature study. Results: Nursing problems identified were: perceptual sensory disorder (auditory hallucinations) as the core problem, social isolation (withdrawal) as the causa, risk of violent behavior as the effect, and self-care deficit as an accompanying problem. Nursing interventions were conducted using the implementation strategy (SP) 1, 2, and 3 for hallucinations and SP 1 for self-care deficit. Conclusion: After 4 days of nursing implementation, 2 out of 4 nursing diagnoses were resolved: perceptual sensory disorder (auditory hallucinations) and self-care deficit, while social isolation (withdrawal) and risk of violent behavior remained unresolved. Patients with hallucinations are expected to be able to control hallucinations using the methods that have been taught.